2016
DOI: 10.4028/www.scientific.net/kem.708.94
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nb Promoter on the Properties of Cu/ZnO/SBA-15 Catalyst and Performance in Methanol Production

Abstract: Hydrogenation of CO2 provides an alternative route for methanol production and attractive option for CO2 utilization. The present work investigates the synthesis of Cu-based catalyst on mesoporous silica (SBA-15) and promotion of the Cu-based catalyst with niobium (Nb). The addition of Nb promoter enhanced the reducibility and dispersion of the active sites as well as increased the BET and Cu surface areas. The performance of the synthesized catalyst in the hydrogenation of CO2 was evaluated in a fixed-bed mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…17 In this direction, Zabidi et al studied the CO 2 hydrogenation reaction on Cu/ZnO/SBA-15 promoted with 1 wt % Nb. 7 They observed that Nb led to increased dispersion and metallic area of Cu and favored the reducibility of the material. As a result of these modifications, the CO 2 conversion and methanol production were optimized.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…17 In this direction, Zabidi et al studied the CO 2 hydrogenation reaction on Cu/ZnO/SBA-15 promoted with 1 wt % Nb. 7 They observed that Nb led to increased dispersion and metallic area of Cu and favored the reducibility of the material. As a result of these modifications, the CO 2 conversion and methanol production were optimized.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of these modifications, the CO 2 conversion and methanol production were optimized. 7 In contrast, considering the strategy of exploring different synthesis methodologies, Liu et al evaluated the deposition− precipitation, coprecipitation, and impregnation methods to prepare Cu/ZrO 2 catalysts. 9 The Cu/ZrO 2 synthesized by the deposition−precipitation method presented a more uniform particle size distribution, smaller particles, and a larger specific surface area than those prepared by coprecipitation or impregnation methods.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations